A Mathematical Model of Communication between Groups of Circadian Neurons in Drosophila melanogaster - Risau Gusman, Sebastian Luis; Gleiser, Pablo Martin (Sage Publications, 2014)
Fil: Risau Gusman, Sebastian Luis. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina